Internationalizing intermediate microeconomics: collaborative case studies and web-based learning - Galarza, Elsa (2007)
This paper describes an internationally-oriented course module for intermediate microeconomics. We describe the collaboration project as well as the results of implementing it at an U.S. and Peruvian university. In the project, U.S. university students were partnered with comparable students at a Peruvian university to complete a project using web-based learning tools and internet conferencing. Project learning objectives are identified and an outline of the project and assignments is presented. Based on our experiences, we evaluate the project and consider problems and issues that arose. Our results suggest that the current state of web-based technology affords university students many opportunities to productively collaborate with their international counterparts.